Antibacterial properties and toxicity from metallic nanomaterials - Vimbela, Gina V (Int J Nanomedicine, 2017)
The era of antibiotic resistance is a cause of increasing concern as bacteria continue to develop adaptive countermeasures against current antibiotics at an alarming rate. In recent years, studies have reported nanoparticles as a promising alternative to antibacterial reagents because of their exhibited antibacterial activity in several biomedical applications, including drug and gene delivery, tissue engineering, and imaging. Moreover, nanomaterial research has led to reports of a possible relationship between the morphological characteristics of a nanomaterial and the magnitude of its delivered toxicity. However, conventional synthesis of nanoparticles requires harsh chemicals and costly energy consumption. Additionally, the exact relationship between toxicity and morphology of nanomaterials has not been well established. Here, we review the recent advancements in synthesis techniques for silver, gold, copper, titanium, zinc oxide, and magnesium oxide nanomaterials and composites, with a focus on the toxicity exhibited by nanomaterials of multidimensions. This article highlights the benefits of selecting each material or metal-based composite for certain applications while also addressing possible setbacks and the toxic effects of the nanomaterials on the environment.